Peculiarities of socialization candidates for military service in the Armed Forces Ukraine - Chyslitska О.; Kuzmenko, M. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article discusses the features of socialization candidates for military service in the Armed Forces of Ukraine. The analysis of psychological study, identifies the factors affecting the level of socialization.